2018
DOI: 10.1371/journal.pone.0193080
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Sexual Excitation/Sexual Inhibition Inventory for Women and Men (SESII-W/M) and the Sexual Excitation Scales/Sexual Inhibition Scales short form (SIS/SES-SF) in a population-based sample in Germany

Abstract: The Sexual Excitation Sexual/Inhibition Inventory for Women and Men (SESII-W/M) and the Sexual Excitation Scales/Sexual Inhibition Scales short form (SIS/SES-SF) are two self-report questionnaires for assessing sexual excitation (SE) and sexual inhibition (SI). According to the dual control model of sexual response, SE and SI differ between individuals and influence the occurrence of sexual arousal in given situations. Extreme levels of SE and SI are postulated to be associated with sexual difficulties or risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 73 publications
3
19
1
1
Order By: Relevance
“…Both women with ASD and female controls scoring higher on sexual excitation reported better sexual functioning. Comparably, previous research found that in women from the general population higher SES scores were positively correlated with a more positive attitude towards sexuality, higher overall sexual functioning, higher sexual desire, higher sexual arousal, less problems with lubrication and higher orgasm quality [36,43,44]. Although women with ASD had significantly lower sexual inhibition scores than female HCs, no association was found between sexual inhibition and sexual functioning in the ASD women.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Both women with ASD and female controls scoring higher on sexual excitation reported better sexual functioning. Comparably, previous research found that in women from the general population higher SES scores were positively correlated with a more positive attitude towards sexuality, higher overall sexual functioning, higher sexual desire, higher sexual arousal, less problems with lubrication and higher orgasm quality [36,43,44]. Although women with ASD had significantly lower sexual inhibition scores than female HCs, no association was found between sexual inhibition and sexual functioning in the ASD women.…”
Section: Discussioncontrasting
confidence: 61%
“…While SIS1 measures sexual inhibition due to a threat of performance failure, SIS2 assesses sexual inhibition due to a threat of performance consequences, for example, unwanted pregnancy or sexually transmitted diseases [35]. In a first validation study of the German version of the SIS/SES-SF, internal consistencies of α = 0.82 for SES, α = 0.60 for SIS1 and α = 0.70 for SIS 2 were reported [36].…”
Section: Methodsmentioning
confidence: 99%
“…Levels of depression and general anxiety will be measured by the Patient Health Questionnaire 9 [ 66 ] and the Generalized Anxiety Disorder 7 [ 67 ], respectively. Sexual excitation and sexual inhibition will be assessed with a short version of the Sexual Inhibition/Sexual Excitation Scales [ 68 , 69 ]. Compassionate attitude toward one self will be measured by the Self-Compassion Scale [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…7. The SESII-W will be measurement invariant across different groups (e.g., partnered vs. singles; higher vs. lower education; younger vs. older, online version vs. paper-pencil version), as seen in previous studies [36].…”
Section: Plos Onementioning
confidence: 97%